NGS-Based Insights into the Oral Microbiome and Glycemic Control in Pediatric Type 1 Diabetes Mellitus: A Literature Review - Maharsi, Eri Dian; Sudarmono, Pratiwi Pudjilestari; Mukhtar, Diniwati; Fadilah, Fadilah (Babali Publisher, 2025)
Introduction: Type 1 Diabetes Mellitus (T1DM) in children is associated with significant alterations in the oral microbiome that can influence glycemic control and oral health. This study aimed to synthesize current evidence on the composition of the oral microbiome in children with T1DM using Next-Generation Sequencing (NGS) and its association with glycemic parameters. Methods: A structured literature review was conducted on studies published between 2020 and 2025 that utilized 16S rRNA sequencing to compare the oral microbiome of children with T1DM and healthy controls. Results: Across the included studies, dysbiosis was consistently observed, characterized by increased pathogenic taxa (Prevotella, Veillonella) and decreased protective genera (Streptococcus), which correlated with elevated HbA1c levels and poor metabolic control. These findings suggest that hyperglycemia-driven shifts in the oral microbiome may exacerbate inflammation and oral disease risk, potentially forming a bidirectional relationship between glycemic regulation and microbial imbalance. Conclusion: Oral microbiome profiling shows promise as a non-invasive indicator of glycemic status in children with T1DM. Further standardized, longitudinal studies in local populations, particularly in Indonesia, are recommended to validate these findings and support the integration of oral microbiome monitoring into pediatric diabetes management.